PERTANGGUNGJAWABAN HUKUM TERHADAP KEDUDUKAN AKTA OTENTIK YANG DIBUAT SELAMA MASA CUTI (PUTUSAN NOMOR : 1/PTS/Mj.PWN.DKIJakarta/xi/2017) - Stefani Hamdani; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2019)
Notary is a profession that is very required in the field of law. In these case, notary acts as a public official in providing a legal services to the society. Notary has a several function like establishment a company, making a deed, legalizing documents, waarmerking, and other services. But in a reality, there are many notaries still do not meet the applicable terms and conditions, “How Is The Notary’s Responsibility Towards Authentic Deed Position During The Leave” this is the main problem we will disscused in this report. The research method used is a descriptive normative research method, which is based on primary data and secondary data as other supporting data which are analyzed qualitatively. From the results of the study explained that that Drs. Andika, as the reporter, came to the reported office named Netty Maria Machdar with the intention to make a certificate of borrowing and guarantee with a certificate, but by Netty's mother a letter of authorization to sell was made which resulted in a loss. In the Letter Number 04 / Ket.Cuti-MPPN / II / 2015 said that it turned out that Notary Netty Maria Machdar was on leave after knowing the deeds and leave certificate. the notary who made the deed during the leave was found quilty, and the position of the deed was a deed under the hand. Which means the notary who made the deed during the leave was found quilty, and the position of the deed was a deed under the hand.